I spy shapes in art - Micklethwait, Lucy. (New York : Scholastic, 2004)
Presents objects with the shape of a heart, a triangle, a square and other shapes through paintings by such artists as Magritte, Escher, and Matisse.
aa
b
b
Keywords: Geometry in art -- Juvenile literature; Art appreciation -- Juvenile literature; Geometry in art; Shape; Art appreciation